Noplace like home : the literary artist and Russia's search for cultural identity - Singleton, Amy C. (SUNY series, the margins of literature., 1997)
Noplace Like Home uses four masterpieces of Russian literature - Nikolai Gogol's Dead Souls, Ivan Goncharov's Oblomov, Evgenii Zamiatin's We, and Mikhail Bulgakov's The Master and Margarita - to show the successes and failings in Russia's search for home and self. Interdisciplinary in spirit, Noplace Like Home introduces Russian culture for the first time to the field of "home studies," which explores human identity in terms of man's relationship with domestic space. This broad social context, together with general cultural patterns expressed in the novels, encourages readers to consider even the most current events in Russian society - where identity and stability are again key issues - in terms of "home," "homelessness," and "noplace."